Impact of FDI on Employment Generation in India (International Journal of Scientific Research and Management (IJSRM), 2015)
Job creation is one of the main challenges for developing countries. Many people believe that FDI can generate many benefits to help solve the capital shortage problem in developing countries. But in terms of job creation, the effects seem more complicated. It has direct and indirect effect on employment. The effect of the FDI on employment is one the most direct expressions of FDI. A substantial amount of development has been observed in the inflows of Foreign Direct Investment (FDI) in India over the last two decades. The extraordinary growth of FDI in 1990 around the world has made it an essential constituent of development strategy for both, developed and developing countries. However, the most profound effect has been observed in developing nations. Macroeconomists have performed various studies in order to prove that FDI plays an important role in generating employment and improving the economic development.